Thematic Learning Strategy Through an Interactive Approach in Class 2 SDS IT Al Munadi Medan - Nur Aisya Fatma (International Journal of Students Education, 2024)
Learning strategy is the process of selecting and arranging learning activities in a learning unit such as sequence, nature of material, scope of material, methods and media that are most suitable for achieving learning competency. There is a need to choose appropriate learning strategies in thematic learning, especially for lower class children. Choosing the right learning strategy can make it easier for students to achieve competencies or learning goals. The aim of this research is to analyze the teacher strategies used in thematic learning in class II SDS IT Al Munadi Medan. The research results show that teachers use learning strategies through an interactive approach. The research was carried out through observation by interviewing the Principal and Class Teacher (class II) of SDS IT Al Munadi Medan. From the results of interviews, teachers use an interactive approach with the aim of stimulating children to think creatively. The inhibiting factor is that children are not good at socializing, therefore they are reluctant to respond to questions and ask questions so teachers must pay more attention which will make children more confident.